Evaluation of the Level and Duration of SARS-Cov-2 Neutralizing Antibodies in COVID-19 Convalescent Healthcare Workers - Zeena Mousa; Ahmed Abdulamir (The Iraqi Journal of Medical Sciences)
Background: The neutralizing antibodies (nAbs) are the main factor for the protective immunity against viruses. Objective: To evaluate the level and duration of anti-receptor-binding domain (RBD) nAbs for 8 months in convalescent Coronavirus disease-2019 (COVID-19) patients with a history of mild-moderate and severe disease. Methods: Up to 160 sera from COVID-19 convalescent hospital healthcare workers (HCWs) with a history of mild-moderate and severe disease at 1-, 3-, 5-, and 8-month post-recovery using in-house developed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-RBD neutralizing competitive enzyme-linked immunosorbent assay (ELISA). Results: SARS-CoV-2 nAbs persisted till 8 months post-recovery in most convalescent patients, the level of nAbs in severe disease group was higher than in mild-moderate disease group; moreover, anti-RBD nAbs mean concentrations in COVID-19 convalescent HCWs tend to increase over time after infection. Similarly, frequency of samples with positive anti-RBD nAbs also tends to increase over time post-recovery. Conclusion: The protective immunity to SARS-CoV-2 in HCWs was found to last for a long time exceeding 8 months after recovery. The increase in the mean level of nAbs over time in COVID-19 convalescent HCWs might be attributed to the frequent asymptomatic re-exposures in HCWs. Keywords: COVID-19, neutralizing antibodies, anti-RBD nAbs, long-term immunity, SARS-COV-2-RBD neutralizing ELISA assay Citation: Mousa ZS, Abdulamir AS. Evaluation of the level and duration of SARS-Cov-2 neutralizing antibodies in COVID-19 convalescent healthcare workers. Iraqi JMS. 2023; 21(1): 30-42. doi: 10.22578/IJMS.21.1.4